The Influence of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) on Financing at PT. Bank Muamalat Indonesia for the Period 2018-2022 - Iqbal Rafiqi; Zulha Fauli Majdi (Penerbit Hellow Pustaka, 2025)
Banks become intermediary institutions that collect public funds (funding), then distribute them (lending) in the form of financing. This study aims to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) partially and simultaneously on financing at PT Bank Muamalat Indonesia. The method used in this research is descriptive quantitative. The object of this research is the quarterly financial statements of PT Bank Muamalat Indonesia for the period 2018-2022. Data collection techniques using documentation through data analysis using multiple linear regression analysis tests. The results of the t-test analysis show that partially the DPK variable has no influence on financing with a significant value of 0.100 > 0.05 and a calculated t value of 1.748 < t table 2.120. The NPF variable has no influence financing, as the significance value is 0.308 > 0.05 with a calculated t value of 1.054 < t table 2.120. The CAR variable has a significant influence on financing. This is proven by a significant value of 0.00 < 0.05 and a calculated t value of 7.131 > t table 2.120. Simultaneously, the DPK, CAR, and NPF variables have a significant influence on financing. This is proven by the sig-F value of 0.00 < 0.05 and the comparison of calculated F value 21,773 > F table 3.20. The predictive ability of these three variables on financing is 76.6% as shown by the Adjusted R Square, while the remaining 23.4% is influenced by other factors not included in this research.